Acute khat use reduces response conflict in habitual users - Colzato, Lorenza S. (Frontiers Media S.A., 2013)
Khat consumption has become a worldwide phenomenon broadening from Eastern Africa and the south west of the Arabian Peninsula to ethnic communities in the rest of the world. So far, the cognitive effects of khat use are poorly understood and no studies have looked into the relation between acute khat use and cognitive control functions, the way we control our thoughts and goal directed behavior. We studied how acute khat use affects the emergence and the resolution of response conflict, a central cognitive control function. Khat users (n = 11) and khat-free controls (n = 18) were matched in terms of education, sex, alcohol, and cannabis consumption. Groups were tested on response conflict, as measured by the Simon task. In one single session, participants worked through two task blocks: the khat group chewed exclusively khat whereas the khat-free group chewed solely a gum. Results showed that in the second block, which reflects the acute impact of khat, the khat group was better than controls in resolving stimulus-induced response conflict as indexed by a smaller Simon effect. These results suggest that the acute intake of khat may improve participants' ability of handling response conflict.